PENGARUH INDEPENDENSI DEWAN KOMISARIS, REPUTASI AUDITOR, RASIO HUTANG, DAN COLLATERALIZABLE ASSETS TERHADAP KEBIJAKAN DIVIDEN (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di Bursa Efek Indonesia Periode 2009-2011) - Yudi Setiawan; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2014)
The objective of this research is to examine the influences of corporate governance and firm characteristics on dividend policy. In particular, based on  agency theory ,variables which allegedly have influence on dividend policy are board independence, auditor reputation, debt ratio, and collateralizable assets. The population of this research is all of the manufacturing entities listed in Indonesian Stock Exchange during the period of 2009-2011. The sampling method used is purposive sampling. The data is acquired from Indonesian Capital Market Directory (ICMD). Linear regression method is conducted to analyze the data. The empirical results indicate that, partially, board independence and debt ratio have no influence towards dividend policy. Auditor reputation  has significantly positive influence  towards dividend policy. Collateralizable assets show significantly negative influence  towards dividend policy.